Is the concept of 'mental retardation" apt? - Jayaram M (Journal of All India Institute of Speech and Hearing, 1970)
Categorisation has evolved from the models of psychopathology. However, the concept of categorisation had more contacts with the medical model rather than with the other models. In the medical model the labelling of deviant behaviour is termed diagnosis and till 1960, it almost appeared a fashion to label behavioral variations separately and to characterise them. The categorisation process has done predominant havoc in the field of psychology. It is very true that the categorisation process and/or the medical model brought in certain amount of reformation. However, it may not be wise to say that since it has brought in reformation, it is an effective model and/or procedure. Recent empirical investigationsare making obvious the statement that the medical model is inefficient in explaining behavioral disorders. We will now examine the truthfulness of this statement with reference to 'Mental Retardation'.